2017
DOI: 10.3390/su10010028
|View full text |Cite
|
Sign up to set email alerts
|

Green Eco-Driving Effects in Non-Congested Cities

Abstract: Despite technological advances in engines and fuels, the transportation sector is still one of the largest emitters of greenhouse gas (GHG). Driving patterns, including eco-driving techniques, are a complementary measure for saving GHG emissions. Most eco-driving studies so far have been conducted in large cities suffering chronic congestion problems. The aim of this research is therefore to analyse the potential of driver behaviour for reducing emissions in a small non-congested city. Driver performance param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
2
7
1
1
Order By: Relevance
“…This study confirms that drivers can apply eco-driving techniques along urban roads that are crossed by roundabouts and pedestrian crossings to reduce the fuel consumption that is required for sudden acceleration/deceleration [40]. One recommendation for transport planners is to implement a "green wave" of coordinated traffic lights along corridors with intensive traffic flows in order to ensure a constant speed (and reduce sudden accelerations/decelerations) and to relieve roundabouts of major flows and permit eco-driving.…”
Section: Policy Recommendationssupporting
confidence: 66%
“…This study confirms that drivers can apply eco-driving techniques along urban roads that are crossed by roundabouts and pedestrian crossings to reduce the fuel consumption that is required for sudden acceleration/deceleration [40]. One recommendation for transport planners is to implement a "green wave" of coordinated traffic lights along corridors with intensive traffic flows in order to ensure a constant speed (and reduce sudden accelerations/decelerations) and to relieve roundabouts of major flows and permit eco-driving.…”
Section: Policy Recommendationssupporting
confidence: 66%
“…HERA is based on a bottom-up methodology which combines an average speed consumption model adjusted with a segment gradient and information on the spatial distribution, by road segment, of vehicle activity with data on vehicle type (average annual daily traffic-AADT-), driving speeds (mean speed of light and heavy vehicles), physical characteristics of the road (length, gradient, number of lanes), and the composition of the fleet circulating along these roadway types. Since HERA is designed for interurban traffic, the transient process of traffic emission such as acceleration or deceleration is not captured, being more important for urban areas assessment [14,15]. HERA produces several outputs: annual GHG emissions and energy consumption (CO 2 eq/year and MJ/year, respectively), and emissions and energy intensity (CO 2 eq/veh-km and MJ/veh-km, respectively).…”
Section: Hera Methodology: Highway Emissions Assessmentmentioning
confidence: 99%
“…On the other hand, Van Mierlo et al [73] have shown that it is possible to achieve consumption reductions of between 5 and 25% with appropriate fuel-saving driving courses. Coloma et al [74] examined the potential of driver behavior for reducing emissions in a small non-congested city; their results showed that the average CO 2 savings were 17% (gasoline engines) and 21% (diesel engines), while the travel times has been increased of about 7.5%.…”
Section: Ecodrivingmentioning
confidence: 99%